2021
DOI: 10.1002/jgh3.12673
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel diseases in Tamil Nadu: A survey of demographics, clinical profile, and practices

Abstract: BackgroundInflammatory bowel disease (IBD) is increasingly diagnosed in South Asia. This survey by the Tamil Nadu Chapter of the Indian Society of Gastroenterology (TNISG) documents the demography, clinical profile, and therapeutic practices related to IBD in Tamil Nadu.MethodsTNISG members from 32 institutions completed an online cross‐sectional questionnaire on IBD patients from March 2020 to January 2021.ResultsOf 1295 adult IBD patients, 654 had Crohn's disease (CD), 499 ulcerative colitis (UC), and 42 IBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The Indian subcontinent has witnessed a remarkable rise in the incidence and prevalence of IBD over the past few decades 31 . Logistic and financial constraints often confine biologic usage to a limited cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Indian subcontinent has witnessed a remarkable rise in the incidence and prevalence of IBD over the past few decades 31 . Logistic and financial constraints often confine biologic usage to a limited cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Indian subcontinent has witnessed a remarkable rise in the incidence and prevalence of IBD over the past few decades. 31 Logistic and financial constraints often confine biologic usage to a limited cohort of patients. AZA is frequently used as first‐line therapy for maintenance of remission in CD and as second‐line after mesalamine for maintenance of remission in UC.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of adult patients with IBD under treatment with anti‐tumor necrosis factor (anti‐TNF) in Asia differs markedly, from as high as 40% in Japan (in 2021) to as low as 10% in Malaysia (in 2019) 81,82 . A study on pediatric IBD from India reported that biologics were used in 18% of children with an onset <16 years 83 . Data on the use of other biologics such as golimumab, 84 ustekinumab, 85,86 vedolizumab, 87 and tofacitinib in childhood IBD in Asia are lacking.…”
Section: Management Of Pediatric Ibd In Asiamentioning
confidence: 99%
“…81,82 A study on pediatric IBD from India reported that biologics were used in 18% of children with an onset <16 years. 83 Data on the use of other biologics such as golimumab, 84 ustekinumab, 85,86 vedolizumab, 87 and tofacitinib in childhood IBD in Asia are lacking.…”
Section: Biologicsmentioning
confidence: 99%